Information systems for population accounting: legal support in the Russian Federation and the Republic of Belarus - Andrichenko, Lyudmila V; Plyugina, Inna V.; Ablameyko, Maria S.; Bogolejko, Alina M. (Journal of the Belarusian State University. Law, 2020)
In all countries of the world in recent decades there has been an intensive introduction of information technologies in the formation of population accounting systems. This made it possible to transfer the population accounting system to a qualitatively different level: modern technologies allow the collection, processing, storage and transmission of a significantly larger amount of heterogeneous data in a relatively short time, but along with this a lot of questions arose in the legal support of these processes, since such systems process and store a huge amount of personal data. Today in various countries different approaches are used to determine the types of information that should be included in information systems of population accounting. This article analyzes the issues of legal regulation during data collection in population accounting systems in the Russian Federation and the Republic of Belarus and offers suggestions for further development and convergence of the regulatory framework of our countries.